2015
DOI: 10.1017/jfm.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the efficiency of a flexible propulsor using experimental optimization

Abstract: Experimental gradient-based optimization is used to maximize the propulsive efficiency of a heaving and pitching flexible panel. Optimum and near-optimum conditions are studied via direct force measurements and particle image velocimetry (PIV). The net thrust and power scale predictably with the frequency and amplitude of the leading edge, but the efficiency shows a complex multimodal response. Optimum pitch and heave motions are found to produce nearly twice the efficiencies of optimum heave-only motions. Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 46 publications
9
95
2
Order By: Relevance
“…We also predicted that the 0 o angle of attack pitching program would further enhance swimming performance, based on the results of Quinn et al [32], and would lead to more fish-like kinematics than seen in previous studies. Finally, we discuss the significance of these improvements in the context of a whole fish body and propose hypotheses about the mechanisms driving the observed performances.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…We also predicted that the 0 o angle of attack pitching program would further enhance swimming performance, based on the results of Quinn et al [32], and would lead to more fish-like kinematics than seen in previous studies. Finally, we discuss the significance of these improvements in the context of a whole fish body and propose hypotheses about the mechanisms driving the observed performances.…”
Section: Introductionmentioning
confidence: 65%
“…Refer to Quinn et al [32] for a schematic diagram of the system, and photographs of similar versions of the experimental set-up were provided by Lauder et al [19] and Lauder et al [33].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have demonstrated that flexibility can drastically improve propulsive performance, especially when a wing or fin is driven near resonance [51,50,21,54,69]. Several studies even performed optimization to uncover wing properties and/or actuation strategies that deliver peak performance [94,2,57,73,69]. All of the studies mentioned above, though, considered only the simplest material distributions, such as uniform flexibility [33,2,4,51,50,21,57,69] or flexibility that is localized through a torsional joint [84,54].…”
Section: Introductionmentioning
confidence: 99%